MEDIEVAL FORTIFICATION OF THE NORTHEASTERN REGION OF ARMENIA: A GENERAL REVIEW - Aleksanan, Tigran Aleksanovic (History, Archeology and Ethnography of the Caucasus, 2024)
This article examines the medieval fortifications of the northeastern part of the Republic of Armenia, specifically the Berd region (formerly Shamshadin district). The study area borders Chambarak to the south, Ijevan to the west, and the Kazakh, Tovuz, and Getabek regions of Azerbaijan to the north and east. The research draws on excavations of Tavush fortress conducted from 2020 to 2022, field surveys of other medieval fortifications in the region, written sources, and archival materials. The medieval defensive structures in the study area are few, comprising only five fortifications: Nor-berd, Katsaret, Yergevank, Matsnaberd, and Tavush fortress. As crucial components of the region’s defense system, these fortifications are typically mentioned together in written sources and in connection with the same historical events. While the exact dates of their construction remain unknown, historical and archaeological evidence suggests they were built between the 10th and 13th centuries. These fortresses suffered significant damage during the Mongol invasions and were subsequently abandoned. The findings indicate that the fortification principles employed in northeastern Armenia were widespread in the medieval period and characteristic of other regions in Armenia, as well as neighboring Azerbaijan and Georgia. This review highlights the need for comprehensive historical, architectural, and archaeological studies of defensive architecture monuments. Such research can shed light onto various aspects of the history, culture, and architecture of medieval Armenia and the South Caucasus as a whole.